Molecular evaluation of some Amanita ponderosa and fungal strains living in association with these mushrooms in the south western Iberian Peninsula - Salvador, C (2014)
Amanita ponderosa are wild edible mushrooms that grow only in some microclimates, particularly those in the southwestern part of the Iberian Peninsula. Due to the vast diversity of mushrooms in nature, as well as nutrient variability, which is highly dependent on soil type and environmental conditions, it is essential to be able to characterize fungal microbiota that lives in association with mushrooms and to differentiate A. ponderosa strains of different regions for certification purposes. In this study, we characterized the genetic profile of A. ponderosa mushrooms and the fungal strains that live in association with them in their natural habitat and compared the fingerprinting profiles obtained by M13-PCR amplification of the genomic DNA.We found that the predominant fungal isolates living in association with A. ponderosa were Aspergillus spp., Penicillium spp. and Mucor spp. M13-PCR molecular analysis showed that different fungal isolates had different genetic profiles. This approach allowed us to differentiate the different fungi strains isolated from fruiting bodies of A. ponderosa both rapidly and in a reproducible manner and to group them according to genus. Our fingerprinting analyses also distinguished different A. ponderosa mushrooms collected from different regions. Consequently, we conclude that this method is a very discriminatory approach for differentiating both A. ponderosa from different sites and the fungal microbiota that lives in association with these mushrooms.